Исследование влияния стационарных течений на динамические процессы и трансформацию примеси в Азовском море, вызываемые прохождением циклонов - Иванов, В.А.; Фомин, В.В.; Черкесов, Л.В.; Шульга, Т.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
The comparative analysis of the diffusion processes of a contaminating admixture in the Sea of Azov in the presence of hydrodynamical processes generated by a seasonal wind and disturbed by cyclonic formations is carried out by using a 3D nonlinear σ-coordinate model. The comparison of the results of numerical experiments with data on cyclones moving along different trajectories in the field of the seasonal wind is performed. The character of the disturbances induced by a moving cyclone into the stationary currents is studied.